Comparative Analysis of Mechanized Versus Conventional Polishing Protocols for Denture Base Acrylic Resins - Margarida Martins Quezada; Carlos Fernandes; Javier Montero; André Correia; Patrícia Fonseca (Applied Sciences)
Surface roughness is primarily determined by the inherent characteristics of a material, the specific polishing protocol and the manual operator’s dexterity. This research intends to conduct a comparative analysis between a conventional and mechanized polishing protocol concerning surface roughness and its impact on surface topography. Thirty samples were included in this in vitro study: six samples for each type of acrylic resin. All specimens underwent a polishing protocol by a conventional method and a mechanized approach with a controlled polishing tool (CPT). Profilometric measures were extracted: arithmetic mean height (Pa), skewness (Psk) and kurtosis (Pku). The Pa values acquired through both the mechanized and conventional polishing techniques are significantly lower compared to the control group. The mechanized polishing notably yielded higher roughness compared to the control group. Relatively consistent skewness and lower-to-moderate values of kurtosis were found across resin types. Differences in the dispersion and pattern for Pa were not detected between the polishing protocols. The CPT protocol reliably maintains consistent skewness and kurtosis values. The conventional protocol remains significant due to the variations observed in the Pa values obtained.